HUMAN RIGHTS AND LAW ENFORCEMENT: THE USE OF FORCE IN COUNTER TERRORISM - Tubagus Ami Prindani; Imam Subandi; Marthinus Hukom; Fayreizha Destika Putri (Fakultas Hukum, Universitas Diponegoro, 2020)
This paper aims at discussing the legal as well as the human rights impact on the use of force and firearms by law enforcement officers in the event of counter terrorism, case study of the Indonesian National Police Counter Terrorism Special Detachment 88 CT (Densus 88 AT Polri). The discussion focuses on the nature of the use of force as well as the use of lethal firearms by law enforcement officers made possible by international legislation and provisions on human rights. Is it possible that the use of force and lethal weapons is still in line with respecting and upholding human rights? How does the state's accountability in the event of use a force by law enforcement officers? How is the validity of the use of deadly forces in the event of arrest or raids conducted by police? Is it true that human rights are always contrary to police duties?